Impact of coadministration of proton-pump inhibitors and palbociclib in hormone receptor-positive/HER2-negative advanced breast cancer - Di Cosimo, Serena; Pérez-García, José Manuel; Bellet, Meritxell; Dalenc, Florence; Gil Gil, Miguel J.; Ruiz-Borrego, Manuel; Gavilá, Joaquín; Aguirre, Elena; Schmid, Peter; Marmé, Frederik; Gligorov, Joseph; Schneeweiss, Andreas; et al. (The breast, 2024)
Background - The capsule formulation of CDK4/6 inhibitor palbociclib has reduced solubility at gastric pH > 4.5 and may have decreased activity when used with proton-pump inhibitors (PPI). Herein, we report the effect of PPI on palbociclib capsule activity and safety in the PARSIFAL study. - Methods - First-line endocrine-sensitive, hormone receptor-positive (HR+)/human epidermal growth factor receptor 2-negative (HER2-) advanced breast cancer (ABC) patients received palbociclib capsules plus fulvestrant or letrozole. The primary endpoint was progression-free survival (PFS). This post-hoc analysis compared PPI use. Patients were PPI-naïve (N-PPI) if not on PPI during the study, and either early (E-PPI) or long-term PPI (LT-PPI) if on PPI at study entry or for at least ≥⅔ of treatment, respectively. PPI groups were not mutually exclusive. - Results - Among 486 patients, 66.9 % were N-PPI, 13.2 % E-PPI, 18.7 % LT-PPI, and 11.5 % of the PPI users were defined as neither. Median PFS (mPFS) was 29.6 months in the study population, 28.7 months in N-PPI, 23.0 months in E-PPI (Hazard Ratio [HR] 1.5; 95%Confidence Interval [CI] 1.1-2.2; p = 0.024), and 23.0 months in LT-PPI (HR 1.4; 95%CI 1.0-1.9; p = 0.035). By landmark analysis, PPI use was associated with poorer mPFS at 3 and 12 months. Grade ≥3 hematological adverse events occurred in 71.7 % of N-PPI, 57.8 % of E-PPI (p = 0.021), and 54.9 % of LT-PPI (p = 0.003). Dose reductions and dosing delays due to hematological toxicity occurred in 70.8 % of N-PPI, 56.3 % of E-PPI (p = 0.018), and 52.7 % of LT-PPI (p = 0.002). - Conclusions - PPI use may reduce palbociclib capsule toxicity, dose modifications, and clinical activity in HR+/HER2- ABC.